Mycobacterium tuberculosis Rv0309 Dampens the Inflammatory Response and Enhances Mycobacterial Survival - Peng, Yongchong; Zhu, Xiaojie; Gao, Lin; Wang, Jieru; Liu, Han; Zhu, Tingting; Zhu, Yifan; Tang, Xin; Hu, Changmin; Chen, Xi; Chen, Huanchun; Chen, Yingyu; et al. (Frontiers in Immunology, 2022)
To reveal functions of novel Mycobacterium tuberculosis (M. tb) proteins responsible for modulating host innate immunity is essential to elucidation of mycobacterial pathogenesis. In this study, we aimed to identify the role of a putative protein Rv0309 encoded within RD8 of M. tb genome in inhibiting the host inflammatory response and the underlying mechanism, using in-vitro and in-vivo experiments. A recombinant M. smegmatis strain Ms_rv0309 expressing Rv0309 and a mutant Bacillus Calmette-Guérin (BCG)ΔRS01790 strain with deletion of BCG_RS01790, 100% homologue of Rv0309 in BCG, were constructed. Rv0309 was found to localize in the cell wall and be able to decrease cell wall permeability. Purified recombinant rRv0309 protein inhibited lipopolysaccharide-induced IL-6 release in RAW264.7 cells. BCG_RS01790 in BCG or Rv0309 in Ms_rv0309 strain greatly inhibited production of IL-6, IL-1β, and TNF-α in RAW264.7 cells. Similarly, BCGΔRS01790 strongly induced expression of these cytokines compared with wild-type BCG and complement strain, cBCGΔRS01790::RS01790. Further BCG_RS01790 or Rv0309 suppressed cytokine production through NF-κB p65/IκBα and MAPK ERK/JNK signaling. Importantly, BCG_RS01790 in BCG and Rv0309 in Ms_rv0309 strain enhanced mycobacterial survival in macrophages. Mice infected with BCGΔRS01790 exhibited high levels of IFN-γ, TNF-α and IL-1β, and large numbers of neutrophils and lymphocytes in the early stage, and minimal lung bacterial load and inflammatory damage in late stage of the experiment. In conclusion, the cell wall protein Rv0309 or BCG_RS01790 enhanced mycobacterial intracellular survival after infection likely through inhibition of the pro-inflammatory response and decrease of bacterial cell wall permeability, thereby contributing to mycobacterial pathogenesis.